Parafia Rembieszyce w latach 1800–1945. Wybrane zagadnienia - Karkocha, Małgorzata (Przegląd Nauk Historycznych, 2013)
The Parish of St. Peter and Paul in Rembieszyce is located in the province of Kielce, in the commune of Małogoszcz. It was founded in 1438 with the efforts of Odrowąż family, the owners Rembieszyce and surrounding villages. From its inception until today, it was composed of four settlements: Rembieszyce, Karsznice, Mieronice and Wola Tesserowa. The present article discusses the history of the parish Rembieszyce in the years 1800–1945, taking into account such issues as the place of the parish in the church administrative structure, its emoluments, priests and church service, and finally the population of the parish. The basic sources for the research are primarily materials stored in the Archives of the Diocese of Kielce, such as lists of the presbytery funds, inventories fundi instructi, statistical lists concerning the parish, reports, and documents prepared for the sake of the parish representatives pastoral visit to the dean, and reports prepared by those in charge of the parish before visiting the parish by representatives of the diocese. The author has also used documents from the archive of the Parish of Rembieszyce (the parish records registering births and deaths and the parish chronicle). Among the printed sources, one should mention the diocesan directories published regularly in the nineteenth and early twentieth century. Other documents, such as correspondence, complement the present study. Analysis of the source material leads to some interesting conclusions. First and foremost, the parish of Rembieszyce in the nineteenth and first half of the twentieth century was one of the smallest and poorest parishes in the diocese. Low emoluments incumbency in Rembieszyce often caused difficulties in its manning. Suffice it to say that over the nearly 150 years the parish had as many as 25 priests with the title administrator and only one proboszcz, i.e. vicar. Twice it was vacant for lack of candidates willing to take over its management. Throughout the period under research on can observe a small but steady increase in the number of inhabitants of the parish. Larger losses in the population were observed only during the period of epidemics and during World War II. Parish of Rembieszyce was fairly uniform in terms of religious and therefore free from sectarian tensions. The majority of its inhabitants were Roman Catholics. Jews constituted a small percentage of the total population (about 3% in the nineteenth century, less than 4% in the first half of the last century). Other denominations in the parish has also been recorded. Last but not least, among the inhabitants of the parish throughout the period that is in the interest of the present study (with some exceptions) female parishioners statistically dominated male ones. This phenomenon is not only characteristic of the parish under research but occurred throughout the province of Kielce.